The Correlation between Students’ Self-Confidence and Speaking Performance - Andi Mangnguntungi Sudirman; Rusdiana Junaid; Ibo Indira Tamallo (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
The research aims to examine the correlation between students’ self-confidence and speaking performance in SMAN EX Palopo. The researcher implemented quantitative as the research design because the data in this research was correlation design. The sample of this research consist of students MIA 1, MIA 2, MIA 3. The researcher took five samples from each class. The researcher used the students score from spoken test to categorize as samples of this research. To collect the data, the researcher employed two kinds instrument, such as: Speaking Test and questioners. The result of correlation analysis shows that there is no correlation between students’ self-confidence and speaking performance in SMAN EX Palopo. It proofed from p-value (0.088) is higher than α (0.05). Therefore H0 is accepted and H1 is rejected